The Effect of Game-Based Circuit Training Model and Leg Length on 60-Meter Sprint (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2018)
The design of training for children is required to be creative and innovative. One of them is making game-based learning. The purpose of this study was to determine the effect of game-based circuit training models and leg length on the speed of a 60-meter sprint run of students at Jobokuto 1 Elementary School, Jepara. This study uses a sample of grade IV students Jobokuto 1 Elementary School, Jepara, with a total of 38 students. Data collection techniques using sprint 60-meter sprint test. The research method uses experimental research so that the data analysis technique used is the Anova formula with a significance level of 0.05. The results of the research test. There is a difference in the effect of training circuit training with the play model on the result of the sprint speed of 60-meters. There is a difference of influence of leg length with low limb and leg category to result of sprint speed of 60. There is an interaction between the training circuit training method and the leg length to the result of the sprint speed of 60-meters. The conclusion that can be drawn from the results of this study is the athletic game of the color play model is feasible and acceptable or used in the lesson penjasorkes athletic learning materials in Elementary School.